Factors Affecting Cloud Accounting Adoption In SMEs - Amir Hamzah; Dadang Suhendar; Agus Zainul Arifin (Jurnal Akuntansi, 2023)
This study aims to analyze the factors influencing the adoption of Cloud Accounting for SMEs. The sample size in this research is 276 respondents. The research method used is quantitative, where hypotheses are tested, and data is analyzedanalyzed using Smart PLS 3.00. The results of the study indicate that Complexity, Security, Top Management Support, Adequate Resources, Competitive Pressure, Pressure from Trading Partners, Coercive Pressure, Government Support, and Provider Support significantly influence the adoption of cloud accounting. On the other hand, Compatibility, Relative Advantage, and IT Competence do not significantly affect the adoption of cloud accounting.